On-Farm Application of Near-Infrared Spectroscopy for the Determination of Nutrients in Liquid Organic Manures: Challenges and Opportunities - Charlotte Höpker; Klaus Dittert; Hans-Werner Olfs (Agriculture)
Nutrient levels in liquid organic manures (LOM) vary greatly, so it is important to determine the concentrations before field application in order to ensure that fertilisation is tailored to the crop requirements. Precise knowledge of the nutrient content in LOMs is a basic prerequisite for the optimum supply of these nutrients to crops and for avoiding environmental problems caused by over-fertilisation. The constituents of LOMs can be determined on site using various methods. One possibility is near infrared spectroscopy (NIRS). This method is already a common procedure for use in the laboratory. This review deals with the suitability of the use of NIRS for the characterisation of LOMs on farm. For on-farm applications, there are many factors such as the ambient temperature or movements and vibrations of the machines which can influence the measurement with the sensors and thus also the measured values. The influencing factors should therefore be taken into account. The reliability of NIRS systems for the on-farm analysis of liquid manure is verified by the German Agricultural Society. For the tests, various LOMs from different farms are measured with NIRS sensors and the quality of the agreement of the NIRS data with laboratory tests is certified for the respective ingredients for each LOM type. In order to exploit the full potential of the NIRS technology in the future, the indispensable calibrations need to be expanded and improved so that the sensors deliver precise and reproducible results for the different LOM types in practical applications.